BIOHEMIJSKI INDIKATORI INFLAMATORNOG ODGOVORA KOD PACIJENATA SA LEUKEMIJOM I FLEBITISOM POVEZANIM SA PICC-OM: PROCENA OSNOVNOG FAKTORA RASTA FIBROBLASTA U KOMBINACIJI SA TERAPIJOM SVETLOM: Light and bFGF Therapy for PICC-Related Phlebitis in Leukemia - Zhang, Shurong; Yang, Xiaotian; Zhang, Xingxia; Wan, Yan; Yu, Youhuan (Journal of Medical Biochemistry, 2025)
Background: The primary objective was to assess the effectiveness and safety of combined bFGF and light therapy for Peripherally Inserted Central Catheters (PICC) phlebitis, measuring improvements in phlebitis grading and Visual Analogue Scale (VAS) scores; evaluating inflammatory regulation through C-reactive protein (CRP), procalcitonin (PCT), erythrocyte sedimentation rate (ESR), and interleukin-6 (IL-6); and determining quality of life changes using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), to establish whether combined therapy demonstrates statistically significant advantages over standard care.Methods: This retrospective study included leukemia patients aged 18-75 years with PICC-associated phlebitis at Huai'an Second People's Hospital between January 2019 and December 2024. Patients were divided into an intervention group (n=33) receiving combined bFGF and light therapy, and a control group (n=32) receiving standard care. Assessment metrics included phlebitis scores and VAS pain scores evaluated on days 3 and 7; inflammatory markers (CRP, PCT, ESR, IL-6) and QLQ-C30 scores assessed on day 7. Data were analyzed using SPSS 26.0, with t-tests for between-group comparisons (P